Qard –The Good, The Fair, & The Ugly: From an Islamic Finance Perspective - Moilim El Azhar Mdawhoma (Journal of Research in Social Science and Humanities, 2025)
Qard, the Arabic term for "loan," is prominently used in both Islamic and conventional banking, particularly in Arabic-speaking regions. Islamic banks often employ the terms Qard and Qard Hassan interchangeably, with Qard referring to an interest-free loan provided for charitable purposes, and Qard Hassan denoting a benevolent loan aimed at providing financial relief without any expectation of profit. This investigation explores the various forms of Qard as detailed in Islamic literature, emphasizing their adherence to Shari'a principles. Key characteristics include the prohibition of interest, the benevolent intent of the lender, the obligation of the borrower to repay the principal amount, and the requirement for transparency and clarity in loan agreements. The study highlights the applications of Qard in modern Islamic banking, such as personal financing, microfinance, and funding social projects, demonstrating its role in promoting social welfare, economic justice, and mutual assistance within the community. Through this examination, the importance of maintaining ethical lending practices in alignment with Islamic law is underscored, ensuring that the values of compassion, transparency, and fairness remain central to Islamic financial systems.